Perceptions towards corruption and its tendency among public servants case study: Kota Samarahan's Public Service Departments / Faridzul Azli Mohd Tahir and Nurul Hasanah Hussien - Mohd Tahir, Faridzul Azli; Hussien, Nurul Hasanah (2013)
Corruption is a complex phenomenon. Despite numerous attempts to define the term there is hardly any single definition that is ‘sufficiently capacious yet discriminating (Williams 1999) to be accepted to universal satisfaction. Generally, it is defined as ‘the abuse of public power for private gains in violation of rules’ (Rose-Ackerman 1999; Manion 2004). It is also seen as ‘illegal actions undertaken by government officials to enrich themselves...’ (Geddes and Neto 1999). Though quite popular, this is often seen as a ‘narrow’, ‘legalist’ and ‘public-office centered’ definition of corruption, for it does not take into account all forms of corruption. As opposed to the view above, some scholars advanced what is known as ‘the market-centered’ view of corruption. They regard corruption when a civil servant perceives his office as a business seeking to maximize his income from it (Tilman, 1968). There is yet another perspective- ‘the public interest centered’ view about corruption (Abdullah, N. R. W. 2008).